VD_FINDINFO Décision / 2014 / 741 vom 9. Februar 2004 - VD Tribunal cantonal (2004)
EXÉCUTION DES PEINES ET DES MESURES, CONGÉTEMPS LIBRE, RÉVOCATIONEN GÉNÉRAL | 75 al. 1 CP, 84 al. 6 CP, 90 al. 4 CP, 106 RSC, 96 RSC